Lastnosti bukovine in njena raba - Čufar, Katarina (Les (Ljubljana), 2017)
We present the structure as well as biological, physical and mechanical properties of European beech (Fagus sylvatica L.) wood in comparison with that of Norway spruce and selected hardwoods. Fine grain, high homogeneity, low anisotropy, medium to high density, favourable mechanical properties, machining, bonding, and finishing, as well as suitability for bending, are among the main advantages which enable wide use of beechwood. Large amounts of beechwood are currently used as fuel. However, for its optimal use, we should revitalize and increase the production of traditional and new semi-finished products like sawn timber, structural and decorative veneer, composite boards and products of chemical processing. In contrast, for energy purposes we should mainly use the residues from these wood-working procedures. According to the numerous favourable properties of beechwood and fairly good possibilities of increasing its durability, we should focus on the development of innovative products to increase its use for construction purposes in buildings.
Keywords: air drying; beech; drying defects; Fagus sylvatica; gradbeni les; inovativni izdelki; kiln drying; lastnosti lesa; navadna bukev; Slovenia; Slovenija; timber quality; tradicionalna raba lesa; wood